2016
DOI: 10.3171/2015.11.focus15573
|View full text |Cite
|
Sign up to set email alerts
|

Identification of residual tumor with intraoperative contrast-enhanced ultrasound during glioblastoma resection

Abstract: OBJECTIVE The purpose of this study was to assess the capability of contrast-enhanced ultrasound (CEUS) to identify residual tumor mass during glioblastoma multiforme (GBM) surgery, to increase the extent of resection. METHODS The authors prospectively evaluated 10 patients who underwent surgery for GBM removal with navigated ultrasound guidance. Navigated B-mode and CEUS were performed prior to resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 38 publications
(92 reference statements)
0
94
0
2
Order By: Relevance
“…Moreover, CEUS is particularly helpful immediately after ablation, to better depict the completeness of the treatment, and to guide an eventual subsequent ablation of residual viable tissue, as reported in liver ablation and even in brain surgery [98][99][100][101]. Use of CEUS during follow-up might help predict the future reduction of the treated nodules, as CEUS is able to show the exact amount of devascularized nodule treatment, as compared to the whole volume shown at the standard US.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Moreover, CEUS is particularly helpful immediately after ablation, to better depict the completeness of the treatment, and to guide an eventual subsequent ablation of residual viable tissue, as reported in liver ablation and even in brain surgery [98][99][100][101]. Use of CEUS during follow-up might help predict the future reduction of the treated nodules, as CEUS is able to show the exact amount of devascularized nodule treatment, as compared to the whole volume shown at the standard US.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…[10][11][12], and ultrasound (13,14). Photodynamic detection, that is the use of a photosensitive drug or dye that enhances tumor visualization by fluorescence, has been also proposed during removal of HHG.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have shown that US applied to neuronavigation systems improves patient survival in the resection of GBM (13,17). With fusion imaging for virtual navigation, preoperative MR images and real-time intraoperative US scans can be displayed in a coplanar fashion, leading to the direct comparison of the two imaging modalities in terms of dimension, with a continuous updated scaling (7,15,(18)(19)(20).…”
Section: Preoperative Mr Imagingmentioning
confidence: 99%
“…A more practical and cost-efficient tool for planning and guiding surgeries is intraoperative US (7,(12)(13)(14)(15). It enables acquisition of real-time information during and after tumor resection but suffers from several artifacts and lack of training by most neurosurgeons.…”
Section: Preoperative Mr Imagingmentioning
confidence: 99%